Development of Plant Physiology Learning Tool Based on Guided Inquiry - Saidatun Ni’mah (Pascasarjana Universitas Negeri Malang (UM), 2014)
Pengembangan Perangkat Pembelajaran Fisiologi Tumbuhan Berbasis Inkuiri Terbimbing Abstract: The purpose of this research was to produce an instructional materials for Plant Physiology course, including syllabus, lesson plan, worksheet, and assessment instruments, based on guided inquiry. The models of this research was adapted from the ADDIE Model which consists of (1) analysis, (2) design, (3) development, (4) implementation, and (5) evaluation. The results of the validation by experts validator and a small group readability test results showed that the developed instructional materials were categorized “Good”. The results of trials on 39 students showed that the guided inquiry-based learning improved the students’ learning outcomes.Key Words: instructional materials development, plant physiology, guided inquiry Abstrak: Penelitian ini bertujuan untuk menghasilkan perangkat pembelajaran Fisiologi Tumbuhan berbasis inkuiri terbimbing yang meliputi silabus, Satuan Acara Perkuliahan (SAP), Lembar Kerja Mahasiswa (LKM), dan instrumen penilaian. Model penelitian dan pengembangan merupakan hasil adaptasi model pengembangan ADDIE yang terdiri dari (1) analysis, (2) design, (3) development, (4) implementation, dan (5) evaluation. Hasil validasi oleh validator ahli dan hasil uji keterbacaan oleh uji kelompok kecil menunjukkan bahwa perangkat pembelajaran hasil pengembangan berkategori baik. Hasil uji coba lapangan dilakukan pada 39 mahasiswa angkatan 2012/2013 Program Studi Pendidikan Biologi STKIP PGRI Banjarmasin dan menunjukkan bahwa dengan pembelajaran berbasis inkuiri terbimbing dapat meningkatkan hasil belajar mahasiswa.Kata kunci: pengembangan perangkat pembelajaran, fisiologi tumbuhan, inkuiri terbimbing